Excellent response to pasireotide therapy in an aggressive and dopamine-resistant prolactinoma. Issue 2 (August 2019) - Coopmans, Eva C; van Meyel, Sebastiaan W F; Pieterman, Kay J; van Ipenburg, Jolique A; Hofland, Leo J; Donga, Esther; Daly, Adrian F; Beckers, Albert; van der Lely, Aart-Jan; Neggers, Sebastian J C M M
Abstract : Prolactinomas are the most commonly encountered pituitary adenomas in the clinical setting. While most can be controlled by dopamine agonists, a subset of prolactinomas are dopamine-resistant and very aggressive. In such tumors, the treatment of choice is neurosurgery and radiotherapy, with or without temozolomide. Here, we report a patient with an highly aggressive, dopamine-resistant prolactinoma, who only achieved biochemical and tumor control during pasireotide long-acting release (PAS-LAR) therapy, a second-generation somatostatin receptor ligand (SRL). Interestingly, cystic degeneration, tumor cell necrosis or both was observed after PAS-LAR administration suggesting an antitumor effect. This case shows that PAS-LAR therapy holds clinical potential in selective aggressive, dopamine-resistant prolactinomas that express somatostatin (SST) receptor subtype 5 and appears to be a potential new treatment option before starting temozolomide. In addition, PAS-LAR therapy may induce cystic degeneration, tumor cell necrosis or both in prolactinomas.